2017
DOI: 10.3171/2016.6.spine16343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early surgical decompression on functional and histological outcomes after severe experimental thoracic spinal cord injury

Abstract: OBJECTIVE In acute traumatic brain injury, decompressive craniectomy is a common treatment that involves the removal of bone from the cranium to relieve intracranial pressure. The present study investigated whether neurological function following a severe spinal cord injury improves after utilizing either a durotomy to decompress the intradural space and/or a duraplasty to maintain proper flow of cerebrospinal fluid. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 65 publications
3
22
0
Order By: Relevance
“…The popularized phrase coined by the senior author, “Time is spine”, highlights the preclinical 13 , 14 and clinical 15 , 16 success of early surgical decompression, which aims to realign the spinal column and relieve bony or ligamentous spinal cord compression. Decompression of intradural pressure, by durotomy alone or durotomy combined with duraplasty, has also been evaluated in experimental SCI 17 , 18 . Yet mixed results warrant further research on the efficacy and standardization of these practices.…”
Section: Neuroprotective Strategies In Current Carementioning
confidence: 99%
“…The popularized phrase coined by the senior author, “Time is spine”, highlights the preclinical 13 , 14 and clinical 15 , 16 success of early surgical decompression, which aims to realign the spinal column and relieve bony or ligamentous spinal cord compression. Decompression of intradural pressure, by durotomy alone or durotomy combined with duraplasty, has also been evaluated in experimental SCI 17 , 18 . Yet mixed results warrant further research on the efficacy and standardization of these practices.…”
Section: Neuroprotective Strategies In Current Carementioning
confidence: 99%
“…48 Jalan et al suggested that decompressive duraplasty in three levels does not affect functional outcomes after injury, whereas that in five levels may lead to the development of neuropathic pain and increase the volume of lesions. 8 In our research, 4-mm decompressive duraplasty was performed at less than three levels and we noted that neither neuropathic pain development nor increased the volume of lesions. Smith et al suggested that decompression surgery should be performed 4 hours after C5 contusion injury.…”
Section: Discussionmentioning
confidence: 68%
“…P-P-C4.5 membrane transplantation groups during the observation period. Von Frey filament tests with a gradient of bending forces (6,8,10,15,26,60,100,180, and 300 g) were applied to the hind limbs to determine the paw withdrawal threshold as an indicator of sensory recovery. The cutoff threshold to elicit paw withdrawals in healthy rats was set at 60 g, below which withdrawal responses were considered allodynia.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…It creates enormous psychological and economic burdens to an individual's family as well as the society as a whole (Guo et al, 2014;Du et al, 2015;Lu et al, 2015;Wang et al, 2016;Yang and Wang, 2015). In the United States, there are approximately 282,000 people suffering from SCI with an average growth of 17,000 cases annually (Jalan et al, 2016). SCI includes primary and secondary injuries.…”
Section: Introductionmentioning
confidence: 99%